2013
DOI: 10.1002/2013gc005012
|View full text |Cite
|
Sign up to set email alerts
|

Modeling fluid flow in sedimentary basins with sill intrusions: Implications for hydrothermal venting and climate change

Abstract: [1] Large volumes of magma emplaced within sedimentary basins have been linked to multiple climate change events due to release of greenhouse gases such as CH 4 . Basin-scale estimates of thermogenic methane generation show that this process alone could generate enough greenhouse gases to trigger global incidents. However, the rates at which these gases are transported and released into the atmosphere are quantitatively unknown. We use a 2D, hybrid FEM/FVM model that solves for fully compressible fluid flow to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 57 publications
5
70
1
Order By: Relevance
“…Iyer et al (2013) showed that varying the density of methane-bearing fluids does not significantly affect the methane release rates at the surface, at least in single-phase flow models such as ours. We further assume that all released methane is dissolved in the pore fluid without affecting the fluid's physical and thermodynamic properties.…”
Section: Conversion Of Organic Matter and Methane Generationmentioning
confidence: 60%
See 3 more Smart Citations
“…Iyer et al (2013) showed that varying the density of methane-bearing fluids does not significantly affect the methane release rates at the surface, at least in single-phase flow models such as ours. We further assume that all released methane is dissolved in the pore fluid without affecting the fluid's physical and thermodynamic properties.…”
Section: Conversion Of Organic Matter and Methane Generationmentioning
confidence: 60%
“…This table supports Figure 2.B starting with the stratigraphy on the left, followed by sill geometry and depth levels. Each sill in our simulations are considered to have a thickness of 100 m, the most common thickness considered for the Karoo sills (e.g., Aarnes et al, 2010;Iyer et al, 2013). Note that consistent with field observations, the Stormberg Group do not host any major sills (e.g., Chevallier & Woodford, 1999).…”
Section: A Dynamic Porosity/permeability Modelmentioning
confidence: 85%
See 2 more Smart Citations
“…The presence of long-lived seepage through vents from underlying strata Iyer et al, 2013) could also have contributed to the reduced compaction of the vent structure. If these fluids migrated and were trapped in the upper vent structure by the deposition of overlying sealing sediments, overpressure could have developed, which in turn may have inhibited further compaction.…”
Section: Dome Shape and Differential Compaction Modelmentioning
confidence: 99%